Intention on food safety among food handlers at the beach culinary tourism area - Asep Rustiawan; Dyah Suryani (International Journal of Public Health Science (IJPHS), 2021)
Food safety remains a public health issue in developing countries. The theory of planned behavior (TPB) was applied to predict food handlers' intentions to perform safe food-handling practices in food processing. This was a quantitative research with observational analytic methods, using cross sectional approach. The sample consisted of 80 food handlers of locally-run seafood stalls along the coast of Bantul Regency, Special Region Yogyakarta, Indonesia. Data analysis employed Chi-square test. The results showed a very strong relationship between attitudes, subjective norms, and self-efficacy with the food handler's intention to perform hygienic food safety. This study suggested that food handlers must have a strong intention to perform safe food-handling practicing in processing food to protect consumers from potential foodborne diseases.